A search for the Method of Decreasing Attenuation in Integrated Optical Channel - Yang Shuwen (Tongxin xuebao)
Starting from theoretical analysis and analogue experiments on the microwave X-band, we have investigated in this paper the influence of light polarization on the attenuation of an integrated optical channel, and proposed that by proper choosing the mode of optical channel, it is possible to attain smaller attenuation and better characteristics without change of geometrical configuration and electrical profile of the waveguide.